Jonathan Edwards on God and creation - Crisp, Oliver (New York, NY : Oxford University Press, 2012)
In Jonathan Edwards on God and Creation, Oliver D. Crisp considers two central themes in Edwards's thought--namely, his doctrine of God and his understanding of the created order, and how God and creation interrelate. Crisp argues that Edwards offers some truly original insights on these twin loci that have important implications for current theological discussion. What emerges is a picture of Edwards's understanding of God's relationship to the created order that differs in important respects from those offered by several influential recent interpreters. Crisp does not flinch from showing where Edwards made mistakes as well as where he offers fresh insights. Edwards is shown to be at once relevant to current discussion of issues like perfect being theology, panentheism, divine freedom or union with Christ, while remaining something of an idiosyncratic figure whose idealism and commitment to an uncompromising theological determinism can seem out of step with certain modern sensibilities. But, argues Crisp, even if we disagree with the conclusions Edwards reaches, which sometimes jar with our own intuitions about the divine nature or the created order, the clarity, rigor and sheer originality of his thinking offer an important set of themes and ideas with which contemporary theologians can fruitfully engage as they set about the task of constructive theology
Ontology -- The divine nature -- Divine freedom -- Divine aseity -- Divine excellency -- The Trinity -- Panentheism -- Consummation
Includes bibliographical references (pages 245-254) and index
Keywords: Edwards, Jonathan, -- 1703-1758; God (Christianity); Creation; Creationism; Theology, Doctrinal -- United States -- History -- 18th century